BUDAYA ORGANISASI DAN KOMPETENSI KARYAWAN Kajian Teoritis dalam Peningkatan Kinerja Karyawan - SUKRISPIYANTO - (Jurnal Akademika, 2016)
The purpose of writing this article is to explain and explore the theory ofperformance associated with organizational cultural factors and individualcompetencies. Employee performance has become important terminology orconcepts in discussions, especially in encouraging the success of the organizationand human resources. Performance will always be the actual issues in theorganization for any organization's performance is key to the effectiveness of theorganization's success. Employee performance is an important issue and apractical and theoretical standpoint. Employee performance is not only influencedby the employees themselves, but also determined by several factors such asorganizational culture and competencies of individuals where the person works.Competence is a concept in human resource management, which requires greatattention. No business, public or private, to detach themselves when discussingcompetence. Theoretically, supported by several empirical studies, individualperformance is influenced by a number of factors, namely the organizationalculture and individual competencies.Keywords: organizational culture, competence, performance